How to manage intellectual capital configurations to improve firm performance in the internet medical industry - Xiaoya Dai (Vilnius Gediminas Technical University, 2021)
The internet medical industry is a new direction of the medical industry; however, internet medical enterprises have been going through a reshuffling period after 2016 and urgently need to improve their performance. The main aim of this study was to reveal the relationship between intellectual capital (IC) configurations and firm performance and guide ideal IC configuration decision to improve the performance of internet medical enterprises in China. First, a mechanism model was constructed to reveal the effects of IC configurations on firm performance, which is contribution to enrich IC configuration theory research. Then, fuzzy-set qualitative comparative analysis (fsQCA) was used to guide its IC configurations selection currently using data from internet medical enterprises in China from 2012 to 2019. The research is contribution to enrich application research of IC configuration. The results show that IC affects firm performance by means of the configuration; currently ideal IC configurations selection of the internet medical industry should pay attention to human, relationship and physical capital; period and specific business will both affect the choice of IC configuration. The results of this study can deepen managers’ understanding of IC configurations and guide ideal IC configurations selection in the internet medical industry.